Efeitos do laser de baixa intensidade e do exercício físico aeróbio sobre a regeneração do músculo tibial anterior de ratos - Adabbo, Mayna (2012)
The objective of this study was to analyze the effects of Low level laser therapy (LLLT) associated with aerobic physical exercise on the muscle regeneration process during 2 periods of rest after of the muscle injury in rats. Forty rats were divided into 2 groups (A and B), and 4 subgroups each: GC (Control Group) - cryolesioned untreated; GE (Exercise Group) - cryolesioned treated with aerobic physical exercise; GL (Laser Group) - cryolesioned treated with laser; GEL (Exercise and Laser Group) - cryolesioned treated with laser and aerobic physical exercise. The tibialis anterior (TA) of the middle belly was injured by a cooling iron bar (cryoinjury). The animals in Group A remained at rest for 3 days, while Group B remained at rest for 7 days. The laser parameters were: 780 nm, 15 mW, during 10 s, 0.152 J e 3.8 J/cm². Physical exercises with or without laser were performed during 5 days, each session lasting 12 min at a treadmill velocity of 17 m/min. The AT muscles were removed for histological and morphometric analysis. The damage area was significantly smaller for the GEL, when remained at rest for 3 and 7 days respectively, (4.4±0.42 % and 3.5±0.14 %, p < 0.05) compared to GL (18.6±0.64 % and 7.5±0.13 %), GE (21±0.26 % and 8.7±0.32 %) and GC (23.9±0.37 % and 21.4±0.38 %). In addition, the number of blood vessels were significantly higher for the GEL, when remained at rest for 3 and 7 days respectively, (71.2±13.51 % and 104.5±11,78, p < 0.05) compared to the GL (60.6±11.25 and 93.5±16.87), GE (51.6±7.3 and 93.8±15.1) and GC (34.4±2.54 and 65.7±14.1). Therefore, the laser applied before the physical exercise on the treadmill stimulated an angiogenesis and accelerated the process of muscle regeneration.